2002
DOI: 10.1046/j.1460-9592.2002.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillator Dysfunction During and After Magnetic Resonance Imaging

Abstract: This report describes a patient in whom a MRI of the brain was performed without realizing that an ICD had been implanted 8 days previously. Electromagnetic noise induced during the MRI was detected as ventricular fibrillation and nearly caused inappropriate shocks. Charge time during MRI was prolonged. The battery indicator switched to "end of life," but this was reversed by capacitor reformation. These problems could have been avoided by inactivating the ICD prior to MRI. Three months later, the pacing thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 0 publications
0
45
1
1
Order By: Relevance
“…Gimbel et al 22 reported similar findings regarding GEM-II-7273 (no damage), VENTAK-AV-1810, and MINI-IV-1790 (irreversible damage) in patients who underwent inadvertent MRI scanning when no special precautions were taken. Anfinsen et al 23 reported similar findings (ie, battery problems and false arrhythmia detection) with a Prizm-VR-1850 in a patient in whom MRI of the brain was performed without realization that an ICD had been implanted 8 days previously, with false detection of electromagnetic noise during the MRI as ventricular fibrillation.…”
Section: Icd Functionmentioning
confidence: 71%
“…Gimbel et al 22 reported similar findings regarding GEM-II-7273 (no damage), VENTAK-AV-1810, and MINI-IV-1790 (irreversible damage) in patients who underwent inadvertent MRI scanning when no special precautions were taken. Anfinsen et al 23 reported similar findings (ie, battery problems and false arrhythmia detection) with a Prizm-VR-1850 in a patient in whom MRI of the brain was performed without realization that an ICD had been implanted 8 days previously, with false detection of electromagnetic noise during the MRI as ventricular fibrillation.…”
Section: Icd Functionmentioning
confidence: 71%
“…22,30,38 Of greater concern, however, are previous reports of changes in programming and lead thresholds after MRI in patients with permanent pacemaker and ICD systems. 3,25 No programming changes were noted in the present study, likely because of our protocol's avoidance of electronic platforms susceptible to electromagnetic interference through previous in vitro and in vivo testing.…”
Section: Device and Lead Parametersmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] On the basis of this early experience, position statements recommended caution in the performance of MRI in patients with an implanted cardiac device. 32,33 Subsequently, a larger prospective study examined 555 cases of scanning (including thoracic imaging) to assess the risk associated with MRI; no adverse clinical events occurred among the patients who underwent MRI, and the observed setting changes did not require device revision or reprogramming.…”
mentioning
confidence: 99%